Model Hibah Terhadap Anak Angkat Di Tinjau Dari Segi Hukum Islam - Masturi, Ngazis; , Prof. Dr. Absori, S.H., M.Hum; , Wardah Yuspin S.H, M.Kn, Ph.D (2017)
Humans as God's most noble creatures are social beings who can not live aloof or apart from other human groups, to meet those needs a family is formed to continue the offspring. The desire to have a child is a natural and human instinct. But in reality it is not uncommon for a household or family not to get offspring. If a family is not born a child then to complement the element of the family or to continue offspring can be done a legal act that is by lifting children. When a person has passed away, a question arises as to what will happen with those legal relationships, which may be closely related when a person is alive. One of the problems that often arise is about the transfer of property from parents to their children, usually in the form of inheritance, grant or testament. This study aims to determine the position of adopted children according to Islamic Law and formulate a model of grant to adopted children in Islamic Law. The method used in this study is a normative legal method.